Tit-for-tat media : the contentious bodies and sex imagery of political activism - Jacobs, Katrien (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This book examines the visual-sexual turn in social media discourses in the field of online activism with a particular focus on the extraordinary protest years of 2018-2020. Presenting the socially engaged theory of "tit-for-tat media" and including case-studies on activist movements such as the Euro-American alt-right, the pro-democracy movement in Hong Kong, and revolutionary artists in China, this study reveals how visual cultures, including gendered or sexualized imagery, are utilised to influence public perception. By presenting in-depth explorations of online ethnography, interviews with activists and studies of the political histories and urban protests-environments, the volume uncovers how local artists, netizens and citizens are using media and digital imagery in contemporary activism. Covering a broad spectrum of social media content, from hyper-cute manga and cartoons to satirical pornography and sexualized hate-speech, it will be of huge interest to students and scholars of media and communication studies, political communication, sexuality and gender studies"--
Buffalo-man and the pink lion : white male suffering and sexual redemption -- Femininity, fluidity and floods amongst the Flemish new-right -- Pepe the frog, emotion politics and gender inclusivity at the Hong Kong anti-extradition movement -- Tit-for-tat nudity and female-figures at the Hong Kong anti-extradition movement -- Hyper-cute characters and gender wars in mainland China.
Keywords: Internet and activism -- Case studies; Social movements -- Case studies; Social media -- Political aspects -- Case studies; Digital media -- Political aspects -- Case studies; Sex in mass media -- Case studies; Sex role in mass media -- Case studies; SOCIAL SCIENCE / Media Studies; SOCIAL SCIENCE / Gender Studies; POLITICAL SCIENCE / General